2007
DOI: 10.1099/vir.0.83097-0
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of putative virulence motifs on infectious salmon anemia virus surface glycoprotein genes

Abstract: Infectious salmon anemia virus (ISAV) is classified in the genusIsavirus of the family Orthomyxoviridae. Although virulence variation of ISAV can be demonstrated experimentally in fish, virus strain identification is ambiguous because the correlates of pathogenicity and/or antigenicity of ISAV are not well defined. Thirteen ISAV isolates characterized for their ability to kill fish were used to search for markers of virulence on the virus surface glycoprotein genes; haemagglutinin-esterase (HE) and fusion (F) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 35 publications
2
64
0
Order By: Relevance
“…It has been suggested that the diversity of HPR sequences provides antigenic variability (56). HPR was proposed as a virulence marker, with the most virulent strains containing HPR4 (36,37,50,51), but some authors do not agree with that conclusion (65). Although every HPR in Chile has been identified, the most abundant is the genotype 7b, which originates from Norway (35).…”
mentioning
confidence: 99%
“…It has been suggested that the diversity of HPR sequences provides antigenic variability (56). HPR was proposed as a virulence marker, with the most virulent strains containing HPR4 (36,37,50,51), but some authors do not agree with that conclusion (65). Although every HPR in Chile has been identified, the most abundant is the genotype 7b, which originates from Norway (35).…”
mentioning
confidence: 99%
“…Differences in virulence among ISAV strains have been described in several studies [11][12][13][14]. Putatively uncultivable non-virulent ISAV variants (ISAV-HPR0) are characterized by an HE protein carrying a full-length highly polymorphic region (HPR) composed of at least 35 amino acids just upstream of the transmembrane domain [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…This isolate is also reported as HPR21 [22]. The titer was determined according to the SpearmaneKärber method [24] and the lysate was frozen until the challenge.…”
Section: Fish and Viral Culturementioning
confidence: 99%
“…This would permit a primary testing of vaccine formulations, and only the most promising formulations would be advanced to full fish challenge models. The 32 K salmonid cDNA microarray developed by the consortium for Genomics Research on All Salmonids Project (cGRASP) (Gene Expression Omnibus (GEO)-GPL8904) was used to identify genes that were differentially expressed in head-kidneys of Atlantic salmon during the course of an infection with a virulent ISAV NA-HPR4 isolate (also referred as HPR21 in Kibenge et al (2007)) [22]. This isolate was previously shown to cause cumulative mortalities of 92% following an intra-peritoneal (IP) injection in a controlled environment [10].…”
Section: Introductionmentioning
confidence: 99%